MENINGKATKAN PENGUASAAN MAKNA KONOTASI DALAM MENULIS PUISI MENGGUNAKAN MEDIA CROSSWORD PUZZLE BERBASIS DIGITAL - Deri Saputra; Titin Nurhayatin; Rani Siti Fitriani; Ibnu Imam Al Ayyubi; Hadi Ahmad Bukhori; Restiani Muslimah S. (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to improve students' lack of interest in writing and analyze their difficulties in expressing feelings and thoughts in the form of poetry. The ability to master diction in writing poetry is a major concern because it affects the quality of their literary works. This study used an experimental method of pretest-posttest control group design consisting of an experimental class that used digital crossword puzzle media and a control class that used clip card media. The data collection methods used in this research include observation, a pilot test, and a test. The research data were analyzed using descriptive and inferential statistics. The results showed that the experimental class using digital-based crossword puzzle media experienced a significant increase in the ability to master connotation meaning in writing poetry compared to the control class. This indicates that the media helped improve poetry writing skills by using appropriate diction. The use of digital-based crossword puzzle media can improve the mastery of connotational meaning in writing poetry for phase D students at SMP Negeri 1 Wanayasa. Teachers need to prepare the content and layout of the crossword puzzle, provide concept explanations, and involve learners.